Effects of denosumab on bone mineral density and bone turnover in patients with rheumatoid arthritis receiving concurrent glucocorticoids or bisphosphonates. Issue 5 (3rd September 2009) - Dore, Robin K; Cohen, Stanley B; Lane, Nancy E; Palmer, William; Shergy, William; Zhou, Lifen; Wang, Huei; Tsuji, Wayne; Newmark, Richard
Abstract : Objectives: To report results of subgroup analyses of bone mineral density (BMD) and bone turnover markers from a randomised, double-blind, placebo-controlled, phase II study of denosumab, an investigational RANKL inhibitor, in patients with rheumatoid arthritis (RA) concurrently receiving treatment with bisphosphonates or glucocorticoids. Methods: Patients received subcutaneous placebo (n=75), denosumab 60 mg (n=71) or denosumab 180 mg (n=72) at baseline and 6 months. Assessments included dual x-ray absorptiometry scans of the lumbar spine and hip, and determination of levels of serum type I C-telopeptide (sCTx-I) and serum procollagen 1N-terminal peptide (P1NP). Results: Denosumab treatment increased mean lumbar spine and hip BMD and reduced sCTx-I and P1NP compared with placebo through 12 months, regardless of baseline BMD or marker levels or concomitant bisphosphonate or glucocorticoid use. Conclusions: This study extends evidence that denosumab increases BMD and reduces bone turnover in patients with RA and may provide a new therapeutic option for reducing systemic bone loss in patients with RA.